2008
DOI: 10.1007/s10603-008-9070-9
|View full text |Cite
|
Sign up to set email alerts
|

Can Consumers Buy Responsibly? Analysis and Solutions for Market Failures

Abstract: Corporate social responsibility, Incentives, Responsible consumer behaviour, Public policies, Ethical consumption, Standards, Labels,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
88
1
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(98 citation statements)
references
References 44 publications
2
88
1
7
Order By: Relevance
“…Several studies [7,13,[42][43][44] have reported that consumers' knowledge of labels may influence the demand for eco-labeling. According to Brécard et al [13] and Valor [45], knowledge may impact consumers' environmental awareness. For example, in Japan, consumers expressed willingness to buy, as well as WTP for eco-labeled seafood once they were informed about the status of fish stocks [10].…”
Section: Acceptance Of Eco-labeled Fishmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies [7,13,[42][43][44] have reported that consumers' knowledge of labels may influence the demand for eco-labeling. According to Brécard et al [13] and Valor [45], knowledge may impact consumers' environmental awareness. For example, in Japan, consumers expressed willingness to buy, as well as WTP for eco-labeled seafood once they were informed about the status of fish stocks [10].…”
Section: Acceptance Of Eco-labeled Fishmentioning
confidence: 99%
“…The survey exposes that people would respond positively to the idea of purchasing eco-labeled fish, but it does not report what respondents would do in reality when exercising their purchasing power in the supermarket. The following considerations should be taken into account: (1) eco-labeling may not represent the most desirable aspects of seafood in purchase decision-making, regarding factors, such as taste, price, brand and market promotions [12]; (2) only specific sectors of consumers are likely to choose eco-labeled fish ( [6][7][8][9][10][11][12][13]33,34], this study); (3) consumers may be less likely to demand eco-labeled products when they have to consider non-economic criteria, such as spending time or effort [45,52]. Even though some studies reported price as a significant factor affecting the purchase decision of eco-labeled products, there is evidence of consumers agreeing to pay higher prices for eco-friendly options [10,11,13].…”
Section: Acceptance Of Eco-labeled Fishmentioning
confidence: 99%
“…They claim that findings from studies examining the relationship of consumer responses to CSR activities are still debatable. Some studies indicate a clearly positive relationship between consumer responses and firm's CSR actions (e.g., Carvalho et al, 2010;Ellen et al, 2006;Smith & Langford, 2009) and others report that this relationship is "not always direct and evident" (e.g., Fatma & Rahman 2015;Fatma et al, 2015;Valor, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, some studies report a positive relationship between a company's CSR actions and consumers' reaction to that company and its products (Brown & Dacin, 1997;Carvalho et al, 2010;Ellen et al, 2006). On the other hand, some surveys indicate that the relationship between a company's CSR actions and consumers' reactions is not always direct and evident, suggesting numerous factors influence this relationship (Carrigan & Attalla, 2001;Maignan & Ferrell, 2004;Valor, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It is of utmost importance that companies report on this issue, given that access to information is a precondition for the business case to work (Valor, 2008). Yet, this condition is far to being met.…”
Section: Human Rights As a Managerial Issuementioning
confidence: 99%